Participation and Reconciliation Preconditions of Justice - Wildfeuer, Armin G.; Adwan, Sami (Schriften der Katholischen Hochschule Nordrhein-Westfalen, 2011)
In order to make justice work, participation and reconciliation is needed within and between societies, peoples, and nations. In this compilation, authors-senior academics as well as students-- from Bethlehem University, Israel, and the Catholic University of Applied Sciences, Cologne, Germany, contribute to this important field. Thus, to some extent, the book in itself is an example of the subjects it deals with.